Squid meal and shrimp hydrolysate as novel protein sources for dog food - Guilherme-Fernandes, Joana; Aires, Tiago; Fonseca, António J. M.; Yergaliyev, Timur; Camarinha-Silva, Amélia; Lima, Sofia A. C.; Maia, Margarida R. G.; Cabrita, Ana R. J. (Frontiers in Veterinary Science, 2024)
The world’s growing pet population is raising sustainability and environmental concerns for the petfood industry. Protein-rich marine by-products might contribute to mitigating negative environmental effects, decreasing waste, and improving economic efficiency. The present study evaluated two marine by-products, squid meal and shrimp hydrolysate, as novel protein sources for dog feeding. Along with the analysis of chemical composition and antioxidant activity, palatability was evaluated by comparing a commercial diet (basal diet) and diets with the inclusion of 150 g kg-1 of squid meal or shrimp hydrolysate using 12 Beagle dogs (2.2 ± 0.03 years). Two in vivo digestibility trials were conducted with six dogs, three experimental periods (10 days each) and three dietary inclusion levels (50, 100 and 150 g kg-1) of squid meal or shrimp hydrolysate in place of the basal diet to evaluate effects of inclusion level on apparent total tract digestibility (ATTD), metabolizable energy content, fecal characteristics, metabolites, and microbiota. Both protein sources presented higher protein and methionine contents than ingredients traditionally used in dog food formulation. Shrimp hydrolysate showed higher antioxidant activity than squid meal. First approach and taste were not affected by the inclusion of protein sources, but animals showed a preference for the basal diet. Effects on nutrient intake reflected the chemical composition of diets, and fecal output and characteristics were not affected by the increasing inclusion levels of both protein sources. The higher ATTD of dry matter, most nutrients and energy of diets with the inclusion of both by-products when compared to the basal diet, suggests their potential to be included in highly digestible diets for dogs. Although not affected by the inclusion level of protein sources, when compared to the basal diet, the inclusion of squid meal decreased butyrate concentration and shrimp hydrolysate increased all volatile fatty acids, except butyrate. Fecal microbiota was not affected by squid meal inclusion, whereas inclusion levels of shrimp hydrolysate significantly affected abundances of Oscillosperaceae (UCG-005), Firmicutes and Lactobacillus. Overall, results suggest that squid meal and shrimp hydrolysate constitute novel and promising protein sources for dog food, but further research is needed to fully evaluate their functional value.